The effect of finger joint profile and orientation on the strength properties of Timber beam for selected Malaysian timber species / Mohd Azran Razlan - Razlan, Mohd Azran (2016)
The jointing together of timber member plays a very important role in the construction of timber structure because all timber structures are made of elements that must be connected together for the transfer of loads between them. Of the failures observed in timber structures, most are attributed to improper connections design, construction (fabrication) detail, or serviceability. Timber connection can be divided into two categories which are mechanical joints and end joints. For end joints, three possible end-joints might be considered in timber connection; butt joints, scarf joints and finger-joints. Finger-joints offer the best way of joining wood, since they provide high strength, not wasteful of wood and can be manufactured at high production rates. Finger joints are type of structural end joint used in glue laminated timber (Glulam) to form long, continuous lamination out of individual pieces of timber. Finger-joint strength evaluations have been well documented on temperate species. Extensive studies have also been conducted on methods used to finger joint and the effect of finger joint profile to the strength of timber. However, little information is available on finger jointing of Malaysian tropical hardwoods especially finger profile geometry and orientation for optimum strength. This thesis reports on the research work carried out in determining the effect of finger-joint length ( 15 mm and 25 mm), orientations (horizontal and vertical) and species of Malaysian timbers (Kapur, Merpauh, Resak, Bintangor, White Meranti, Sesenduk and Kelampayan) on the strength properties of finger jointing as connections in timber beams. The bondability of adhesive to timber, thick adherend shear test and contact angle were conducted. Non-destructive test (NDT) was also performed. The results showed that there is no significant difference in the joint strength of the beams for all species in terms of finger lengths and orientations. The failure modes of the failed bending specimens were observed and it was found that timbers in lower strength groups (SG 6 and SG7), failed mostly in timbers. However for higher strength groups’ timber (SG 4 and SG5) the failures were mostly in adhesive failure. These results correlate well with the thick adherend shear test and contact angle tests. The NDT tests were conducted to see if this method can be used to predict the MOE of finger jointed beam. The test results for NDT tests showed that is no correlation in the dynamic MOE and static bending MOE.